Analisis Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Nasabah Pada Koperasi Simpan Pinjam Lego-Lego Kalabahi Kabupaten Alor (Studi Kasus Pada Koperasi Simpan Pinjam Lego-Lego Kalabahi Kabupaten Alor) - Moikalong, Ediwatna; Awang, Mesak Y.; Anigomang, Ferdinand Romelus; Maruli, Elia (Jurnal Ilmiah Wahana Pendidikan, 2023)
Ediwatna Moikalong (2023) thesis title Analysis of the Effect of Service Quality Dimensions on Customer Satisfaction of KSP Lego-Lego Kalabahi, Alor Regency Supervisor I: Elia Maruli, SE., MM and supervisor II: Dr. Hermayanti. This study aims to determine the effect of the dimension of service quality on customer satisfaction, This type of research is quantitative research with data collection techniques, namely observation, interviews, and documentation studies. This study uses primary population data and the sample is customers who are making loans at KSP Lego-Lego Kalabahi, Alor Regency totaling 30 customers. And the sampling technique in this study is purposive sampling technique. The statistical method used in this study is multiple linear regression. The results of this study show that: (1). Partially, the physical evidence variable has a significant value of 0.038 where this value is smaller than the alpha value of 0.05 so that the results of this study receive H1 which states that partial physical evidence has a positive effect on customer satisfaction at the Lego-Lego Kalabahi KSP, Alor Regency. (2). Partial reliability variable has a significant value of 0.001 where this value is smaller than the alpha value of 0.05 so that the results of this study accept H2 which states that partial secarah reliability has a positive effect on customer satisfaction at Lego-Lego Kalabahi KSP, Alor Regency. (3). The partial responsiveness variable has a significant value of 0.001 where this value is smaller than the alpha value of 0.05 so that the results of this study receive H3 which states that partial responsiveness has a positive effect on customer satisfaction at the Lego-Lego Kalabahi KSP, Alor Regency. (4). The partial empathy variable has a significant value of 0.008 where this value is smaller than the alpha value of 0.05 so that the results of this study receive H4 which states that partial empathy has a positive effect on customer satisfaction at the Lego-Lego Kalabahi KSP, Alor Regency. (5). The partial collateral variable has a significant value of 0.026 where this value is smaller than the alpha value of 0.05 so that the results of this study receive H5 which states that partial collateral has a positive effect on customer satisfaction at the Lego-Lego Kalabahi KSP, Alor Regency. (6). Simultaneously, the variables of physical evidence, reliability, responsiveness and empathy and assurance have a significant value of 0.000, where this value is smaller than the alpha value, namely H6, which states that the variables of physical evidence, reliability, responsiveness and empathy simultaneously have a positive effect on customer satisfaction at the Lego-Lego Kalabahi KSP, Alor Regency.